Da Voce a Voce: spazio etico o spazio politico da Tiresia di Giuliano Mesa a Terraemotus di Fabio Orecchini (ENTHYMEMA, 2020)
Historical removal is the crux in which the poem Tiresia by Giuliano Mesa and Terraemotus installation by Fabio Orecchini meet each other. The tragic of the Twentieth century that has been removed, what we prefer not to see, is the blind prophet Tiresias’ object of vision: mass graves, atomic bombs, trade in infant organs, exploitation of children, slums. In a rhythmic-visionary spiral, linguistic rigor is measure of ethical rigor.
Keywords: Giuliano Mesa; Fabio Orecchini; contemporary Italian poetry; experimental poetry; engaged literature